Relasi Popularitas Jeans dan Musik - Rendy Pandita Bastari; Patra Aditia; Atria Nuraini Fadilla (JURNAL RUPA, 2019)
In the 19th century jeans were popular among the lower classes, this transmitted to the upper classes that made jeans as a commodity. The social class shift made Jeans as part of popular culture which was then consumed in Indonesia along with television shows, magazines and films. The process of data collecting and field observations was carried out at two popular shopping malls in the city of Bandung, Cihampeas Walk and Paris Van Java. These observations strengthened by sub-cultural and musical analysis and popular culture in Indonesia. The findings of this study are that music has influenced the popularity of jeans models for decades, music lovers and popular culture constitute the majority who have an ideology about a goal that forms their own aesthetics. This finding is closely related to the position of Bandung which has always been known as a trendsetter city in Indonesia.